Estimation of Phosphorus Storage in Seagrass in the Coastal Waters of Eastern and Northen Bintan Island - Luthvi Nurwulandari; Apriadi, Tri; Zulfikar, Andi (Journal of Marine and Coastal Science, 2025)
The eastern and northern coastal waters of Bintan Island are seagrass conservation areas with high biodiversity and coverage. Seagrass is known to play an essential role in the carbon cycle and has the potential to store phosphorus, but limited information is available regarding its phosphorus reserves. This study aims to estimate phosphorus (P) storage in seagrass and analyze the relationship between seagrass ecological parameters and phosphorus content. A field survey and hierarchical sampling technique were conducted at six locations, with samples of seagrass, substrate, and water analyzed in laboratory. Results showed the highest seagrass density in Pengudang (816 shoots/m²) and the lowest in Berakit 2 (107 shoots/m²); the highest coverage in Teluk Bakau 1 (83.5%) and the lowest in Teluk Bakau 2 (43.1%); and the highest biomass in Pengudang (138.55 gr/m²) and the lowest in Berakit 2 (19.39 gr/m²). The highest phosphorus storage was recorded in Berakit 2 (0.321%) and the lowest in Teluk Bakau 2 (0.258%). A positive correlation was observed between coverage and phosphorus content, indicating that increased seagrass coverage potentially enhances phosphorus storage capacity. These findings offer new insights into the role of seagrass in the phosphorus cycle and its implications for sustainable coastal ecosystem management.